Increasing drug compliance to hypertension patients through android applications in Wonosobo regency province of Central Java Indonesia - ., Suyoto; Agushybana, Farid; Suryoputro, Antono (International Journal Of Community Medicine And Public Health, 2019)
Background: Based on data from WHO, it is estimated that 70% of the 57 million deaths that occurred in the world in 2008 were caused by non-communicable diseases. The prevalence of cases of hypertension primary in the District of Wonosobo in the year 2016 as many as 43.30%. Hypertension patients must take medication during their lifetime to prevent rising blood pressure and complications. This research aims to find out the effect of hypertension management through an android application on the practice of adherence to taking medication in hypertensive patients in Wonosobo regency. Methods: This research is a quasi-experimental with a non-randomized pre-post-test control group design. The study is conducted in patients prolanis hypertension as much as 105 respondents were divided into a treatment group 53 respondents and group control of 52 respondents. Results: Results of the study showed the significant influence of the use of android application to practice obedience to drink medicine. Results of Mann Whitney U analysis showed the treatment group experienced a rise in the mean is higher than the group of control. Likewise, the results of the test Wilcoxon which compares the level of compliance before and after treatment obtained value significantly for both groups with a mean group of treatment is higher. Conclusions: The management of hypertension through an android application has proven to be more effective in improving the practice of adherence to taking medication hypertension patients who take part in the prolanis program in Wonosobo regency.